Biblical wisdom: rethinking Christian education according to Proverbs 1:2-7 and its relationship with national education philosophy - Nassa, Grace Son; Latuihamallo, Yulianus (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2023)
The purpose of this study is to discover the significance of biblical wisdom according to Proverbs 1:2-7 in Christian education and to use it as a point of view when highlighting the national education philosophy, as well as to see whether the nature of the two complement each other or sharpen each other when they meet? The method used was a combination of theological interpretation of Proverbs 1:2-7 and a synchronic perspective on the philosophy of the national education motto. This research found that Christian education has two sides when it meets the philosophy of the national education motto. First, Christian education remains based and aims at biblical wisdom, next, it can be open to the philosophy of the motto but applies analytical rigor and criticality.